EKOLINGUSTIK METAFORA DALAM LAGU MELAYU SAMBAS KARYA BULYAN MUSTHAFA - Purnawati, Lusi; Heryana, Nanang; Jupitasari, Mellisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research was conducted by analyzing the Malay song Sambas by Bulyan Musthafa with the aim of knowing the forms of metaphor in the song and its relation to the environment in which it was formed. The method used in this study is a descriptive method with a qualitative research form. The data sources for this research are 14 songs by Bulyan Mustafa which are divided into two albums in two different YouTube channels. The data in this study are in the form of song lyrics that contain metaphorical forms. The research technique used is observational technique and documentary study. The first data collection tool used is writing instruments, the second is a mobile device, and the third is a laptop. Based on the data analysis conducted in the Malay Song Sambas by Bulyan Musthafa, there are several forms of metaphor that are related to the environment in which they are formed. The form of learning text related to Ecolinguistic Metaphor in Bulyan Mustafa's Malay Song Sambas is an E-Module of Poetry Text that will be adapted to the 2013 curriculum learning at the X grade high school level.